MANUFACTURING VIRGIN COCONUT OIL (VCO) THROUGH THE SALT METHOD - Silalahi, Lora; Daniel, Gilbert (Jurnal Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the effect of adding CaCl2 salt on the yield results. Old coconuts taken are 12 months old. 12 coconuts are grated to produce 600 kg of grated coconut and then filtered to produce 1200 mL of coconut milk. Add 2 grams, 4 grams and 6 grams of CaCl2 to each coconut milk and stir for 10 minutes. Coconut milk is heated at 100°C for 120 minutes using a hotplate. Then coconut oil was produced and an organoleptic test was carried out with the results of a typical coconut aroma, clear color and tasteless taste of the coconut oil. Then to produce the best yield it is 23.20% and the optimum water content is 2 grams with a concentration of 0.17%. The higher the CaCl2 level, the greater the yield of VCO produced and the water content produced will be of good quality. The best quality VCO is VCO that does not use contaminated or old coconut, has a distinctive coconut aroma and fresh taste, does not contain odor or taste. which is unusual and the color is relatively clear and clear. Meanwhile, poor quality VCO means using chemicals or excessive heating during extraction, it doesn't smell fresh or tastes strange, the color is cloudy or too dark and contains additives or other additives that shouldn't be there.